Third-party Intervention in Civil Wars and the Prospects for Postwar Development. (March 2017) - Kim, Sang Ki
How does third-party intervention in civil war influence citizens' physical quality of life (QOL) after civil war? I find that the effects of intervention on postwar QOL depend on its type, unilateral intervention, and United Nations (UN) intervention. Unilateral interveners seeking self-interest tend to impede the improvement in postwar QOL particularly in terms of life expectancy and infant mortality rate. They are likely to do so through producing their protégé's military victory or negotiated settlement, expanding their influence on postwar government, and resultingly forming a government less responsive to citizens' hardship and reducing resources available for welfare. UN intervention on humanitarian grounds tends to promote postwar social development particularly in the fields of public health, although it has no significant effect on literacy rate. It is likely to do so by increasing resources available for postwar reconstruction, even though it goes where postwar social development is relatively difficult.